In-situ monitoring of glass fiber/epoxy composites by the embedded multi-walled carbon nanotube coated glass fiber sensor: From fabrication to application - Wan, Y.; Hu, W.; Yang, L.; Wang, Z.; Tan, J.; Liu, Y.; Yang, B.
Monitoring the curing defects as well as damages that occur in the fabrication and application process is important for ensuring the safety of composite structures. In this paper, a highly sensitive 1-D line sensor is designed to achieve self-sensing and diagnosing functionalities in both the fabrication and application of glass fiber reinforced epoxy (GF/epoxy)composites. The sensor consists of multi-walled carbon nanotube coated glass fiber (MWCNT@GF), which is sensing the damage by the principle of resistance change. Due to the vacuum-assisted resin infusion process, the MWCNT@GF sensor is embedded into GF/epoxy composite laminates, and hence, it can monitor the resin frontal flow, curing, and especially the flow defects. In the subsequent application, the tensile performance of a GF/epoxy composite joint is evaluated by not only the force-displacement curve but also the displacement-dependent resistance change of the sensor. Tensile damage modes are distinguished, which is for the first time to be reported. The MWCNT@GF sensor is mechanically stable and highly sensitive; hence, it can be used to follow the composite performance from fabrication until the end of life.
Keywords: COMPOSITE JOINT; CURING MONITORING; IN-SITU MONITORING; MWCNT@GF SENSOR